Functionality and reliability improvement of lifting mechanism system in the drone docking station using TRIZ - Salim, Mohd Azli; Muhammad, Rawaida; Akop, Mohd Zaid; Md. Saad, Adzni; Photong, Chonlatee (UTHM Publisher, 2024)
Drone docking station (DDS) is a hub designed for drone origin resting that is used for highway surveillance. The studied DDS is purposely for low-cost and locally sourced DDS components used in remote areas to store and protect the drone. This paper aims to select simpler design of lifting mechanism that can improve the functionality and reliability of the DDS by using TRIZ tools. The key solutions are obtained using the Function Analysis (FA) tool and Engineering Contradiction (EC) tool. By utilizing FA tool, functions of all DDS components were identified and it helped to focus on improving the chosen subsystem which is the lifting mechanism. After that, by applying EC tool, a screw type or known as mechanical type lift was chosen as the lifting mechanism for the DDS. The EC tool shows that the mechanical lifting mechanisms have simpler design with no dependency on fluid making it more suitable to be installed inside the DDS. By selecting the mechanical lifting mechanism, the simplicity design relates with easier maintenance and troubleshooting procedures, without risk of fluid-related issues. However, it should be tested in real working environments to find and fix any underlying problems.